The Effect of Water Extract of Salam Koja Leaf (Murraya koenigii (L.) spreng) Against Root-Knot Nematode (Meloidogyne spp.) in Tomato Plants - Sunarto, Toto; Angelia, Brigitta (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2022)
Root-knot nematodes (Meloidogyne spp.) is one of the pathogens that attack tomato plants so that it can reduce tomato production. One alternative to control Meloidogyne spp. environmentally friendly is to use botanical nematicides. Salam Koja (Murraya koenigii (L.) Spreng) has potential as a botanical nematicide because its leaves contain secondary metabolites which are antihelmintic. The purpose of this study was to determine the effect of water extract of M. koenigii leaves and to obtain the best concentration in suppressing the attack of Meloidogyne spp. on tomato plants. This research was conducted at the Greenhouse, Department of Plant Pests and Diseases, Faculty of Agriculture, Universitas Padjadjaran, Jatinangor. The study used an experimental method with a randomized block design consisting of 6 treatments and 4 replications. The treatments included control (without water extract of M. koenigii leaves), concentrations of water extract of M. koenigii leaves 6%, 9%, 12%, 15%, and carbofuran 2 g/plant. The results showed that the water extract of M. koenigii leaves had an effect on suppressing root-knot nematodes (Meloidogyne spp.) on tomato plants. The water extract of M. koenigii leaves at the highest concentration of 15% is effective in suppression of the number of galls in the roots (38.57%) and suppression of the number of juvenile 2 (J2) Meloidogyne spp. in 100 ml of soil (81.03%). Murraya koenogii leaf water extract can be used to control Meloidogyne spp. in tomato plants.